Association between perfluoroalkyl substance concentrations and blood pressure in adolescents. (November 2019) - Ma, Siyu; Xu, Cheng; Ma, Ji; Wang, Zhiqi; Zhang, Yuxi; Shu, Yaqin; Mo, Xuming
Abstract: The effects of exposure to some environmental chemicals on blood pressure have been determined, but the association between non-occupational exposure to perfluoroalkyl substances (PFASs) and blood pressure in adolescents remains unknown. The association between blood pressure and PFAS concentrations was studied by analysing data from 2251 participants filtered from the population enrolled in the National Health and Nutrition Examination Survey (NHANES) from 2003 to 2012. After adjusting for age, sex, race, BMI, cotinine level, dietary intake of calcium, caloric intake, sodium consumption, potassium consumption and sampling year, we estimated the coefficients (betas) and 95% confidence intervals (CIs) for the relationship between PFAS concentrations and blood pressure with multiple linear regression models. Potential non-linear relationships were assessed with restricted cubic spline models. Blood levels of perfluorooctane sulfonic acid (PFOS) had a strong positive association with diastolic blood pressure (DBP) in adolescents in the linear model, while the result was not significant in the non-linear model. No significant association was observed between the concentration of any other PFASs and blood pressure. According to the fully adjusted linear regression model (P = 0.041), the mean DBP values in boys in the higher PFOS quintile were 2.70% greater than the mean DBP values of boys in the lowest PFOS quintile. Furthermore, serum PFOS concentrations predominantly affected blood pressure in male adolescents compared with female adolescents. These results provide epidemiological evidence of PFOS-related increases in DBP. Further research is needed to address related issues. Graphical abstract: Image 1 Highlights: 2251 adolescents were used to examine associations of polyfluoroalkyl chemicals with blood pressure levels. Positive associations were found between blood PFOS and diastolic blood pressure in males. Restricted cubic spline models showed no significant associations between PFOS and blood pressure. Abstract : Low-dose exposure to PFOS is positively related to elevated diastolic blood pressure in male adolescents.